The assessment of Cyclophosphamide Chemotherapy Effect Loading-PLGA Nanoparticles Against Ovarian Cancer Cells Line (OVCAR-4 and PEO1) (Journal of Pharmaceutical Negative Results, 2022)
Our study aimed to ameliorate the efficacy of anticancer drug of Cyclophosphamide on ovarian cancer cell lines related to human by loadingwith poly (D,L lactic-co-glycolic acid) (PLGA) which considered as nanoparticles (NPs) material. The merge of Cyclophosphamide – PLGANPs were done by the technique of nanoprecipitation. NPs was prepared equal scattered with an average diameter of 133±25.19 nm. The doseresponse curves of free Cyclophosphamide dose were orgnized (12.5-2000 uM) by using the assay of MTT on OVCAR-4 and PE01 cell linesfor 1 ,3 and 5 days. IC50 on OVCAR-4 was calculatrd and were 178 uM after one day of exposure , 15.3 uM and 1.38 uM after three andfive days respectively. On the other hand, the IC50 on PE01 was only noticed after five days of exposure for Cyclophosphamide (11.70 uM).The viability of OVCAR-4 after treatment with Cyclophosphamide at 100 uM with free or with PLGA NPs consctruction for three days was41.4% and 14.9% respectively. Resemblance, when 250uM was applied, the viability of OVCAR-4 was 19.2% and 11.8% after wxposure tofree and NPs forms of Cyclophosphamide. In addition , the cell viability of PE01 when 250 uM applied ,the free or NPs constructions was55.45% and 37.21% respectively. Oue work showed that OVCAR-4 cell line was more susceptible to Cyclo-PLGA NPs as compared to PE01cells. conclusion : our action manifested that the effcet of Cyclophosphamide is time-depended and the protract effect originate by PLGA NPsmay give a share in, at least to boost and increase efficacy of Cyclophosphamide as anticancer activity drug